Species occurrence and distributional ecology of nearshore cetaceans in the Bay of Bengal, Bangladesh, with abundance estimates for Irrawaddy dolphins Orcaella brevirostris and finless porpoises Neophocaena phocaenoides - Smith , Brian D. S; Ahmed , Benazir; Mowgli , Rubaiyat Mansur; Strindberg, Samantha (J. Cetacean Res. Manage., 2023)
A vessel-based line-transect survey conducted during February 2004 along 1,018km of systematic trackline in the nearshore waters of Bangladesh resulted in 111 ‘on-effort’ cetacean sightings including: Irrawaddy dolphins, Orcaella brevirostris (n=75, mean group size=2.2); finless porpoises, Neophocaena phocaenoides (n=11, mean group size=2.6); Indo-Pacific humpback dolphins, Sousa chinensis (chinensisform; n=6, mean group size=16.2); Indo-Pacific bottlenose dolphins, Tursiops aduncus (n=3, mean group size=36.1); pantropical spotted dolphins, Stenella attenuata (n=1, best, high and low group size estimates=800, 1,100 and 600, respectively); Bryde’s whales, Balaenoptera edeni/brydei (large-form; n=1, three individuals); and unidentified small cetaceans (n=14). Cetacean distribution was closely tied to environmental gradients, with Irrawaddy dolphins and finless porpoises occurring most often in nearshore, turbid, low-salinity waters, IndoPacific humpback dolphins in slightly deeper waters where the colour turned from brown to green and Indo-Pacific bottlenose dolphins and Bryde’s whales in deep, clear, high-salinity waters of the Swatch-of-No-Ground (SoNG), a 900+m-deep submarine canyon that extends to within about 40km of the Sundarbans mangrove forest. A Generalised Additive Model of environmental and presence-absence data indicated that Irrawaddy dolphin distribution was conditionally dependent (p<0.05) on low salinity and shallow depth, which explained 36% of the variance. A distance analysis of Irrawaddy dolphin and finless porpoise sightings resulted in abundance estimates of 5,383 (CV=39.5) and 1,382 (CV=54.8%), respectively. The positive conservation implications of these abundance estimates were tempered by observations of potentially unsustainable bycatch in gillnet fisheries targeting elasmobranches and scarring on bottlenose dolphins consistent with trawl fishery interactions. The nearshore waters of Bangladesh support a taxonomically diverse and relatively abundant cetacean fauna, which can probably be explained by the wide variety of environmental gradients (river-sea and shallow-deep) available within a relatively small area and the enormous biological production driven by extreme fluvial and oceanographic processes. Priority recommendations for future research include: (1) evaluating bycatch levels and the types of fishing gears responsible for incidental kills; (2) investigating the spatial and temporal dynamics of high-density cetacean hotspots; (3) resolving the species and population identities of baleen whales and delphinids occurring in the SoNG; and (4) assessing the abundance, movement patterns and fishery interactions of Indo-Pacific bottlenose dolphins.